Riverlands of the Anthropocene : walking our waterways as places of becoming - Somerville, Margaret (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Riverlands of the Anthropocene invites readers into universal questions about human relations with rivers and water for the precarious times of the Anthropocene. The book asks how humans can learn through sensory embodied encounters with local waterways that shape the architecture of cities and make global connections with environments everywhere. The book considers human becomings with urban waterways to address some of the major conceptual challenges of the Anthropocene, through stories of trauma and healing, environmental activism, and encounters with the living beings that inhabit waterways. The book's unique contribution is to bring together Australian Aboriginal knowledges with contemporary western, new materialist, posthuman, and Deleuzean philosophies. It foregrounds how visual, creative and artistic forms can assist us in thinking beyond the constraints of western thought to enable other modes of being and knowing the world for an unpredictable future. Riverlands of the Anthropocene will be of particular interest to those studying the Anthropocene through the lenses of environmental humanities, environmental education, philosophy, ecofeminism and cultural studies"--
A blue literature review -- Rivers of the Anthropocene -- Watery beginnings -- Walking the songlines of the singing painting river -- Riverland's watery ways -- Bedrock's sacramental becomings -- The river's crossing -- Global materialities: and the artful excess of river's litter -- Regeneration: of trees, weeds and tender intimacies -- Life and death in the Anthropocene.
Includes bibliographical references and index.
Keywords: Rivers -- Environmental aspects; Human ecology; Geology, Stratigraphic -- Anthropocene; Australian